Effects of a contrast training program without external load on vertical jump, kicking speed, sprint, and agility of young soccer players - Garcia-Pinillos, F.; Martinez-Amat, A.; Hita-Contreras, F.; Martinez-López, E. J.; Latorre-Román, P. A. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this study was to determine the effects of a 12-week contrast training (CT) program (isometric + plyometric), with no external loads, on the vertical jump, kicking speed, sprinting, and agility skills of young soccer players. Thirty young soccer players (age, 15.9 ± 1.43 years; weight, 65.4 ± 10.84 kg; height, 171.0 ± 0.06 cm) were randomized in a control group (n = 13) and an experimental group (n = 17). The CT program was included in the experimental group's training sessions, who undertook it twice a week as a part of their usual weekly training regime. This program included 3 exercises: 1 isometric and 2 plyometric, without external loads. These exercises progressed in volume throughout the training program. Performance in countermovement jump (CMJ), Balsom agility test (BAT), 5-, 10-, 20-, and 30-m sprint, and soccer kick were assessed before and after the training program. A 2-factor (group and time) analysis of variance revealed significant improvements (p < 0.001) in CMJ, BAT, and kicking speed in the experimental group players. Control group remained unchanged in these variables. Both groups significantly reduced sprint times over 5, 10, 20, and 30 m (p < 0.05). A significant correlation (r = 0.492, p < 0.001) was revealed between ?BAT and ?average kicking speed. Results suggest that a specific CT program without external loads is effective for improving soccer-specific skills such as vertical jump, sprint, agility, and kicking speed in young soccer players.